MRI‐guided celiac plexus neurolysis for pancreatic cancer pain: Efficacy and safety. Issue 4 (28th March 2016) - Liu, Shangang; Fu, Weiwei; Liu, Zengjun; Liu, Ming; Ren, Ruimei; Zhai, Huaxu; Li, Chengli
Abstract : Purpose: To prospectively determine the efficacy and safety of magnetic resonance imaging (MRI)‐guided celiac plexus neurolysis (CPN) for pancreatic cancer pain. Materials and Methods: In all, 39 patients with pancreatic cancer underwent 0.23T MRI‐guided CPN with ethanol via the posterior approach. The pain relief, the opioid intake, and pain interference with appetite, sleep, and communication in patients were assessed after CPN during a 4‐month follow‐up period. The complications were also evaluated during or after CPN. Results: CPN procedures were successfully completed for all patients. Minor complications included diarrhea (9 of 39; 23.1%), orthostatic hypotension (14 of 39; 35.9%), and local backache (20 of 39; 51.3%). No major complication occurred. Pain relief was observed in 36 (92.3%), in 15 (40.5%), and in 11 (35.5%) patients at 1‐, 2‐, and 3‐month visits, respectively. The median duration of pain relief was 2.9 months (95% confidence interval [CI], 2.4–3.4). The opioid intake significantly decreased at the 1‐, 2‐, and 3‐month visits ( P < 0.001, < 0.001, = 0.001 respectively), and there was significant improvement in sleep at the 1‐, 2‐, and 3‐month visits ( P < 0.001, < 0.001, = 0.001 respectively), and appetite and communication were significantly improved at the 1‐ and 2‐month visits (all P < 0.001); all compared with baseline. Conclusion: MRI‐guided CPN appears to be an effective and minimally invasive procedure for palliative pain management of pancreatic cancer. J. MAGN. RESON. IMAGING 2016;44:923–928.